Strategi Implementasi BUMDes Dalam Perspektif Inklusi Sosial (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
The exclusivity of persons with disabilities contributes to village poverty. BUMDes is an extension of the village government which has a role in improving welfare, alleviating village poverty and unemployment. The implementation of inclusive BUMDes is important as one of the government's efforts, especially the village government, to reduce poverty problems caused by the exclusivity of persons with disabilities. BUMDes Jaga Karsa is the most inclusive BUMDes with the best title in Situbondo Regency. Based on this, this study tries to analyze the implementation strategy of BUMDes Jaga Karsa in the perspective of social inclusion by involving the disability community, in this case Situbondo Disability Care Pioneer Community (PPDiS). The research method used is a qualitative description. All data was obtained through observation, interviews, FGDs and documentation. The results of this study are that BUMDes implement three important aspects in their management, first, aspect of fulfilling physical and non-physical accessibility such as the construction of disability-friendly public toilets, ramp stairs, handrails to information disclosure. Second, aspects of identity through recognition of persons with disabilities. Third, aspects of freedom of opinion and choosing a job position, and an emphasis on the participation or involvement of persons with disabilities in drafting village regulations that are pro-disabilities as part of village development. These three points are the basic things that distinguish the management of BUMDes Jaga Karsa from other BUMDes in the Situbondo district. Keywords: BUMDes, disability, exclusivity, social inclusion.